(untitled) (Al-Academy, 2023)
The impact of television has made it an essential technology that can’t be dispensed with in all circumstances and situations, measuring the society’s need for it. Some argue that there is no stronger media than television in introducing people of the world to each other, as it has the most powerful impact and attracts millions of viewers.Television is deemed as the most effective tool of media as it is designed to capture both sound and image. The image, in itself, has the ability to engage and interact with our thoughts. In light of the aforementioned, it is noticeable that this interactive medium (television) has significantly evolved over the years, thanks to modern technologies that have been introduced over time. These advancements have added an element of credibility between both the broadcaster and the audience’s interaction. It has been made possible through live broadcasts, transmissions, and the presenter’s presence at the scene of the event at the time of its occurrence.Television is the main source of news for the majority of people in various contemporary societies. The television and news programs still constitute the main center of gravity in the process of influencing viewers, and in particular when watching the news bulletin on (any channel), we quickly expect to see the news, reports and polls offered by the bulletin that affect the life of our society.The purpose of news bulletins is to inform viewers about the current events happening in the local community, the nation as a whole, and even at the global level. It is presented through the medium of television, aided by a team of professionals such as the directors, presenters, correspondents, cameramen, sound recordists, lighting technicians and editors, who work together to create a coherent and engaging news bulletin